Pengaruh Kebijakan Perberasan, Pertumbuhan Ekonomi dan Kebijakan Fiskal terhadap Kemiskinan di Indonesia - Dudi Septiadi; Pande Komang Suparyana (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2019)
Poverty is an urgent problem to be overcome immediately because not only includes economicproblems but also social problems and domestic political instability. Poor population is the populationwho are unable to meet the minimum basic food and non-food needs. This study aims to analyze thefactors that affect poverty in Indonesia and analyze rice policy, economic growth and fiscal policy onpoverty alleviation in Indonesia. This research method used multiple regression analysis with timeseries data from 1988 - 2017. The results showed that statistically, the coefficient of determination(R2) was quite high. Based on the F-statistic test, all independent variables simultaneously have asignificant effect on the dependent variable. Based on partial siginification test, Indonesian riceproduction variable, Indonesian total rice import variable, government purchase price variable on ricecommodity and economic growth variables respectively have a significant effect on poverty variable.The elasticity values of Indonesian rice production variable, Indonesian total rice import variable,government purchase price variable on rice commodity and economic growth variable has elasticityvalues that are inelastic. While the variable government spending on infrastructure has no effect on thepoverty variable.